Medicines and vaccines for the world's poorest: Is there any prospect for public-private cooperation? - Scheffler Richard M; Pathania Vikram (BMC, 2005)
Abstract This paper reviews the current status of the global pharmaceutical industry and its research and development focus in the context of the health care needs of the developing world. It will consider the attempts to improve access to critical drugs and vaccines, and increase the research effort directed at key public health priorities in the developing world. In particular, it will consider prospects for public-private collaboration. The challenges and opportunities in such public-private partnerships will be discussed briefly along with a look at factors that may be key to success. Much of the focus is on HIV/AIDS where the debate on the optimal balance between intellectual property rights (IPR) and human rights to life and health has been very public and emotive.